Analisis Reduplikasi Pada Cerpen Guru karya Putu Wijaya - Muhammad Arifin; Mimin Trianjani; Zulfa Sofiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the use of reduplication in the short story "Guru" by Putu Wijaya. Reduplication is a morphological process that involves repeating part or all of the basic form of a word to create a new meaning or give a certain effect. The purpose of this study is to identify the types of reduplication used in the short story "Guru" by Putu Wijaya and to analyze its function and meaning in the narrative context in detail. The method used is qualitative descriptive analysis with a linguistic approach. The results of the study indicate that reduplication in this short story is used to emphasize the atmosphere, describe the characters, and provide rhythm to the story. These findings indicate that reduplication not only functions grammatically, but also has artistic and narrative value in it.